VALUATION PADA INITIAL PUBLIC OFFERING (IPO) BANK BRI SYARIAH - Mulkan, Mulkan; Herawati, Aty (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
Adding the number of ownership by issuing new shares and selling them to the capital market, is one alternative method used with the aim of increasing the Company’s finances, funds and capital. The issuance of the company’s initial shares and selling them to the capital market is called the Initial Public Offering. BRI Syariah Bank adds capital by conducting an IPO, so that it is necessary to analyze Stock Prices on the Initial Public Offering (IPO) of BRI Syariah Bank to obtain stock fair value that does not harm the company if the stock price is too low or detrimental to investors due to stock prices too high (over valued). The research problem formulation is: How is the valuation of the initial stock price of BRI Syariah Bank using the Relative Valuation Model method, How is the valuation of the initial stock price of BRI Syariah Bank with the Free Cash Flow to Equity (FCFE) method, and Is the initial stock Under Valued or Over Valued. The researcher analyzed the data obtained using quantitative descriptive methods. The value of Bank BRI Syariah shares calculated using the Relative valuation method and FCFE are in an overvalued position. The initial stock decision taken by the company is correct, that is, if the valuation is done using the Relative Valuation and FCFE methods, the company is already due because the stock price in the market is overvalued.